Etiological Profile of Atrial Fibrillation (AF) In Nepalgunj Medical College: A Hospital Based Study - Kidwai, A (Journal of Nepalgunj Medical College, 2018)
Introduction: Atrial fibrillation (AF) is the commonest cardiac arrhythmia encountered in clinical practice. The hall mark sign of atrial fibrillation is an irregular rhythm in ECG with no obvious P wave. In Western countries, Coronary Artery Disease (CAD) is the commonest cause of AF. Plenty of data and studies are available regarding the epidemiology and etiology of AF in the Western Population but similar studies and data in Nepal are scarce. This study was therefore conducted with an objective to establish the etiological profile of atrial fibrillation patients in mid western Nepal. Materials and Methods: This was a hospital based study, carried out in the Department of Internal Medicine, Nepalgunj Medical College Teaching Hospital, Nepalgunj, for a duration of 1 year from th th 14 September 2013 to 13 September 2014. A total of 74 consecutive cases diagnosed as AF were included in the study on the basis of inclusion and exclusion criteria. Results: A total of 74 consecutive patients were included in the study. The mean age of the subjects was 39.2 years. The majority of the subjects were below 50 years of age (70.27%). There were only 2 subjects below 19 and 3 patients above 70 years of age. Out of the 74 patients 52(70.2%) were from the age group of below 50 years of age. In western countries the incidence is higher in the elder population. Rheumatic heart disease was the most common etiology in this study with a total of 29 (39.2%) cases. CAD in our study was seen in 12 patients (16.2%). Overall structural heart disease was seen in 64(86.5%) cases and in the rest of the cases echocardiography was normal. Conclusion: This study has shown that the etiological profile of AF is different in patients attending our hospital situated in mid-western Nepal from western countries. Unlike the western countries AF is more common in the younger age group and the most common etiology in Nepal is RHD, whereas in western countries it is CAD. JNGMC, Vol. 14 No. 2 December 2016, Page: 23-25